Sleep specialist – defined phenotypes in healthcare staff: a cross-sectional study (International Journal of Occupational Safety and Health, 2026)
Introduction: Healthcare professionals face irregular work schedules and sleep disruption. Identifying sleep–function phenotypes may support early prevention and occupational performance.Methods: Exploratory, cross-sectional study aimed to characterize sleep parameters and work-related conditions through certified sleep-specialist interviews, defining clinically meaningful sleep phenotypes in healthcare workers. This single-center cross-sectional study was conducted between December 2021 and February 2022 in a tertiary hospital. Interviews captured occupational and sleep-related parameters by a sleep specialist. Validated Greek versions of the Pittsburgh Sleep Quality Index (PSQI), Athens Insomnia Scale (AIS), and Epworth Sleepiness Scale (ESS) were administered. Data collection involved structured questionnaires and statistical analysis using STATA/IC software.Results: Among 38 healthcare professionals, most were medical/nursing staff (71%), one-quarter worked rotating shifts (26%), and the majority reported short sleep duration (74%